Percutaneous Versus Surgical Insertion of Peritoneal Dialysis Catheters: A Systematic Review and Meta-Analysis. (November 2021) - Agarwal, Anirudh; Whitlock, Reid H.; Bamforth, Ryan J.; Ferguson, Thomas W.; Sabourin, Jenna M.; Hu, Qiming; Armstrong, Sean; Rigatto, Claudio; Tangri, Navdeep; Dunsmore, Sara; Komenda, Paul
Background: Home-based peritoneal dialysis (PD) is an alternative to facility-based hemodialysis and has lower costs and greater freedom for patients with kidney failure. For a patient to undergo PD, a safe and reliable method of accessing the peritoneum is needed. However, different catheter insertion techniques may affect patient health outcomes. Objective: To compare the risk of infectious and mechanical complications between surgical (open and laparoscopic) PD catheter insertion and percutaneous catheter insertion. Design: Systematic review and meta-analysis. Setting: We searched for observational studies and randomized controlled trials (RCTs) in CENTRAL, EMBASE, MEDLINE, PubMed, and SCOPUS from inception until June 2018. Data were extracted by 2 independent reviewers based on a preformed template. Patients: Adult (aged 18+) patients with kidney failure who underwent a PD catheter insertion procedure. Measurements: We analyzed leak, malfunction, and bleed as early complications (occurring within 1 month of catheter insertion). Infectious complications (exit-site infections, tunnel infections, and peritonitis) were presented as both early complications and with the longest duration of follow-up. Methods: Random effects meta-analyses with the generic inverse variance method to estimate pooled rate ratios and 95% confidence intervals. We quantified heterogeneity by using the I2 statistic for inconsistency and assessed heterogeneity using the χ 2 test. Sensitivity analysis was performed by removing studies at high risk of bias as measured with the Newcastle-Ottawa Scale and the Cochrane Risk of Bias tool. Results: Twenty-four studies (22 observational, 2 RCTs) with 3108 patients and 3777 catheter insertions were selected. Data from 2 studies were unable to be extracted and were qualitatively assessed. In the remaining 22 studies, percutaneous insertion was associated with a lower risk of both exit-site infections (risk ratio [RR] = 0.36, 95% confidence interval [CI] = 0.24-0.53, I 2 = 0%) and peritonitis (RR = 0.52, 95% CI = 0.36-0.77, I 2 = 3%) within 1 month of the procedure. There was no difference in mechanical complication rates between the 2 techniques. Limitations: Lack of consistency in the time periods for the various outcomes reported, risk of bias concerns with respect to population comparability, and the inability to analyze individual component causes of primary nonfunction (catheter obstruction, catheter migration, and leak). Conclusions: Our meta-analysis suggests differences in early infectious complications in favor of percutaneous insertion and no significant differences in mechanical complications compared with surgical insertion. These findings have implications on the direction of PD programs in terms of maximizing operating room resources.